Analisis Perbandingan Jaringan One Stage dan Two Stage Fiber to The Home - Putri Amanda, Azizah; Maruddani, Baso; Setyowati, Arum (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2022)
The purpose of this research is to find out the best internet network quality in the one-stage and two-stage Fiber to The Home network by knowing the FTTH network parameters, the parameters used are Link Power Budget, Bit Error Rate (BER), Q-Factor, and Quality of Service (QoS). In analyzing an FTTH network, it uses a qualitative content analysis method. The results show that the single-stage network is better when viewed from the manual calculation of total attenuation, but the attenuation results can also be with those in the field. The results of the manual calculation of the link power budget of the two stages to get a downlink of -22.98088dBm and uplink to get -23.7436dBm. The results of the manual calculation of the link power budget for one stage for downlink are -22.90088dBm and uplink are -23.6636dBm.